Fecal Microbiota and Gut Microbe-Derived Extracellular Vesicles in Colorectal Cancer - Park, Jihye; Kim, Nam-Eun; Yoon, Hyuk; Shin, Cheol Min; Kim, Nayoung; Lee, Dong Ho; Park, Jae Yong; Choi, Chang Hwan; Kim, Jae Gyu; Kim, Yoon-Keun; Shin, Tae-Seop; Yang, Jinho; et al. (Frontiers in Oncology, 2021)
Background and Aims Human microbiota comprises trillions of microbes, and the relationship between cancer and microbiota is very complex. The impact of fecal microbiota alteration on colorectal cancer (CRC) pathogenesis is emerging. This study analyzed microbial composition changes in CRC subjects with both fecal microbiota and gut microbe-derived extracellular vesicles (EVs). Methods From August 2017 to August 2018, 70 CRC patients and 158 control subjects were enrolled. Metagenomic profiling of fecal microbiota and gut microbe-derived EVs in stool was performed by 16S ribosomal DNA sequencing. Relative abundance, evenness, and diversity in both gut microbiota and gut microbe-derived EVs was analyzed. Additionally, microbial composition changes according to the stage and location of CRC were analyzed. Results Microbial composition was significantly changed in CRC subjects compared to control subjects, with evenness and diversity significantly lower in CRC subjects in fecal microbiota. Gut microbe-derived EVs of stool demonstrated significant differences in microbial composition, evenness, and diversity in CRC subjects compared to control subjects. Additionally, microbial composition, evenness, and diversity were significantly changed in late CRC subjects than in early CRC subjects with both fecal microbiota and gut microbe-derived EVs. Alistipes - derived EVs could be novel biomarkers to diagnose CRC and predict CRC stages. Ruminococcus 2 - derived EVs was significantly decreased in the distal CRC subjects than proximal CRC subjects. Conclusions Gut microbe-derived EVs in CRC had a distinct microbial composition compared with controls. Profiling of microbe-derived EVs may offer a novel biomarker for detecting and predicting CRC prognosis.